Nilai Tambah Produk Olahan Jahe Merah pada UD. VisionBali Herbal Indonesia, Denpasar - ROSO, ARIEF SETIAWAN; SUAMBA, I KETUT; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.2, April 2017, 2017)
The Added Value of Processed Red Ginger Product at UD. VisionBali Herbal Indonesia, Denpasar This research aimed to determine the added value of red ginger as an herbal drink in one production process and to determine the level of profits earned by the company in the red ginger processing in one production process. Determination of the study area was done purposively and the analytical methods used was the method of added value calculation, i.e. the product value is deducted by the value of raw materials and other supporting materials. It can be concluded from the result of the research that the added value of the red ginger processing business obtained in one production process is Rp. 84.600,00/kg. The added value is obtained from the deduction of the value of the product/output of Rp. 175.000,00/kg with the cost of raw material (input prices) Rp. 25.000,00/kg and the contribution of the cost of other inputs of Rp. 65.400,00/kg. It was also found that the profits gained by the manufacturer from the processed red ginger into herbal drink in one production process was Rp. 200.954,06. The suggestion that can be given to the company is to put more attention in the details of its production costs so as not to result in a low ratio of added value and further to improve the marketing of the products, so that people are interested in re-use of herbal medicine that is free of chemical components.
Keywords: Red Ginger; the added value